Search for long-lived particles decaying to leptons with large impact parameter in proton-proton collisions at s = 13 Te - Tumasyan, A; Adam, W; Andrejkovic, J W; Bergauer, T; Chatterjee, S; Damanakis, K; Dragicevic, M; Valle, A Escalante Del; Frühwirth, R; Jeitler, M; Krammer, N; Lechner, L; et al. (The European physical journal. C, Particles and fields, 2022)
A search for new long-lived particles decaying to leptons using proton-proton collision data produced by the CERN LHC at s = 13 Te is presented. Events are selected with two leptons (an electron and a muon, two electrons, or two muons) that both have transverse impact parameter values between 0.01 and 10 cm and are not required to form a common vertex. Data used for the analysis were collected with the CMS detector in 2016, 2017, and 2018, and correspond to an integrated luminosity of 118 (113) fb - 1 in the e e channel ( e μ and μ μ channels). The search is designed to be sensitive to a wide range of models with displaced e μ , e e , and μ μ final states. The results constrain several well-motivated models involving new long-lived particles that decay to displaced leptons. For some areas of the available phase space, these are the most stringent constraints to date.